Music streaming dalam industri musik era industri 4.0 - Amanda, Rissa (Jurnal Studi Komunikasi, 2022)
Industrial era 4.0 shows that all human activities will be connected and dominated by digital media. Creativity and new ideas to innovate technology are the keys of this era. For example in the music industry 4.0, which develops music streaming technology products, trying to attract a lot of millennials generation. In the context of Indonesia, Langit Musik as a local product competes with Spotify as an international product. Therefore, through this literature review-based research and interview with some of the participants in Whatsapp phone call, researchers want to see what kind of music streaming platform in the industrial era 4.0 make many peoples interested, especially the millennials generation in Indonesia. The results show that the use of Spotify in Indonesia is still more popular than Langit Musik, because for most of the Indonesian millennial generation Spotify is already suitable for the music streaming criteria they want. These include a diverse and global selection of songs, from old songs to the latest songs that are always up-to-date, have a simple and eye-catching display, easy to use, clear sound quality, have lyrics for karaoke, integrated with social media for status updates, have playlist personalisation feature, and no need to use large mobile data internet quota. However, Spotify and Langit Musik are still not able to attract their customers to switch from free to premium services, due to different needs and there are people who are still comfortable downloading songs illegally even though they already had music streaming. Spotify has become more popular than Langit Musik because of consumer trust in its quality, besides that personal promotion by word-of-mouth from the closest people and status updates on social media, which also support the expansion of Spotify’s popularity.